2013
DOI: 10.1007/s12262-013-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

“Uncommon Contents of Inguinal Hernial Sac”: A Surgical Dilemma

Abstract: Inguinal hernia repair is the most common surgery done by both young and experienced surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…The commonest content in hernia sac was small bowel followed by omentum the ndings are consistent with study of Amos et al and 12,13 Goyal et al .…”
Section: Table 3: Postoperative Complications and Outcomesupporting
confidence: 90%
“…The commonest content in hernia sac was small bowel followed by omentum the ndings are consistent with study of Amos et al and 12,13 Goyal et al .…”
Section: Table 3: Postoperative Complications and Outcomesupporting
confidence: 90%
“…Goyal et al, in their prospective study on uncommon contents of inguinal hernial sac, reported that small bowel as the most common content in inguinal hernias followed by omentum, the observations are similar to the findings of present study. 18 Bekoe in his prospective review of 118 patients with incarcerated/strangulated inguinal hernias stated that he could find "no definite criterion" to differentiate incarcerated hernia with viable contents from the non-viable contents and cannot be diagnosed on clinical grounds. 19 Obstruction is associated with 50% risk of bowel ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis can be easily confirmed by ultrasonography scan in most cases. However, for better anatomical illustration and details of the hernias and its boundaries as well as contents magnetic resonance imaging (MRI) and computed tomography (CT) scan can be done [7]. The current case was successfully diagnosed preoperatively by ultrasound.…”
Section: Discussionmentioning
confidence: 95%